Characterization of Ceftazidime-Avibactam-Resistant Carbapenem-Resistant Enterobacteriaceae, United States, 2015–2017. (October 2020) - Ansari, Uzma; Reses, Hannah E.; Grass, Julian; Nadle, Joelle; Bower, Chris; Jacob, Jesse; Vaeth, Elisabeth; Witwer, Medora; Hancock, Emily; Dale, Suzanne; Dumyati, Ghinwa; Beldavs, Zintars; et al.
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) are a major public health problem. Ceftazidime-avibactam (CZA) is a treatment option for CRE approved in 2015; however, it does not have activity against isolates with metallo-β-lactamases (MBLs). Emerging resistance to CZA is a cause for concern. Our objective was to describe the microbiologic and epidemiologic characteristics of CZA-resistant (CZA-R) CRE. Methods: From 2015 to 2017, 9 states participated in laboratory- and population-based surveillance for carbapenem-resistant Escherichia coli, Klebsiella pneumoniae, K. oxytoca, K. aerogenes, and Enterobacter cloacae complex isolates from a normally sterile site or urine. A convenience sample of isolates from this surveillance were sent to the CDC for antimicrobial susceptibility testing (AST) using reference broth microdilution (BMD) including an MBL screen, species confirmation with MALDI-TOF, and real-time PCR to detect bla KPC, bla NDM, and bla OXA-48–like genes. Additional AST by BMD was performed on CZA-R isolates using meropenem-vaborbactam (MEV), imipenem-relebactam (IMR), plazomicin (PLZ), and eravacycline (ERV). Epidemiologic data were obtained from a medical record review. Community-associated cases were defined as having no healthcare exposures in the year prior to culture, no devices in place 2 days prior to culture, and culture collected before calendar day 3 after hospital admission. Data were analyzed in 3 groups: CRE that were CZA-susceptible (CZA-S), CZA-R that were due to bla NDM, and CZA-R without bla NDM. Results: Among 606 confirmed CRE tested with CZA, 33 (5.4%) were CZA-R. Of the CZA-R isolates, 16 (48.5%) harbored a bla NDM gene, of which 2 coharbored bla NDM and bla OXA-48-like genes; 9 (27.3%) harbored only a bla KPC gene. Of the 17 CZA-R isolates without bla NDM, all were MBL screen negative. CZA-R due to bla NDM were more frequently community-associated (43.8%) than CZA-S or CZA-R without bla NDM (11.0% and 5.9%, respectively); a higher percentage of CZA-R cases due to bla NDM also had recent international travel (25%) compared to the other groups (1.8% and 5.9%, respectively). CZA-R without bla NDM were more susceptible to MEV (76%), IMR (71%), PLZ (88%), and ERV (65%) compared to CZA-R due to bla NDM (19%, 6%, 56%, and 44%, respectively). Conclusions: The emergence of CZA-R isolates without bla NDM are concerning; however, these isolates are more susceptible to newer antimicrobials than those with bla NDM. In addition to high rates of resistance to newer antimicrobials, isolates with bla NDM are more frequently community-associated than other CRE. This underscores the need for more aggressive measures to stop the spread of CRE. Funding: None Disclosures: None